Асимптотичні властивості розв'язків систем нелінійних диференціально-функціональних рівнянь нейтрального типу - Вельгач, А.В. (Нелінійні коливання, 2009)
Установлены достаточные условия существования непрерывно дифференцируемых и ограниченных при t ∈ R (вместе с первой производной) решений систем нелинейных дифференциально-функциональных уравнений нейтрального типа и исследованы их асимптотические свойства. We establish sufficient conditions for existence of solutions, which are continuously differentiable and
bounded together with their first derivatives for t ∈ R of a system of nonlinear neutral type differentialfunctional equations, and study asymptotic properties of the solutions.